Propriedades físico-químicas de cimentos Portland e à base de MTA associados ao Aloe vera - Zina, Omar (2013)
The aim of this study was to determine the solution-powder ration and to evaluate the setting time, solubility, dimensional change, pH and radiopacity of White structural and non-structural Portland cement, ProRoot MTA® and MTA BIO® associated to 2% glycolic solution of Aloe vera. Five samples of each material were used for each test according to American National Standards Institute/American Dental Association specification 57. Statistical analyses were carried out using ANOVA and Tukey’s test at 5% level of significance. When sample distribution was non-normal, nonparametric analysis of variance were performed with Kruskal-Wallis test (α=0.05). The results revealed no statistical difference in the water-powder ratio among the tested materials. ProRoot MTA® had the longest setting time (116.50 ± 4.08) (P<0.05). White structural and nonstructural Portland cements did not have means values on the radiopacity test (109.76 ± 10.40 and 118.75 ± 15.44, respectively) in accordance with ANSI/ADA, being significantly different from the MTA-based cements (P<0.05), and demonstrated higher mean solubility values (2.30 ± 0.36 and 2.81 ± 0.40, respectively) (P<0.05). The values for dimensional change of all tested materials were considered acceptable by ANSI/ADA. There were no significant differences between the mean pH values recorded for the materials (p>0.05). It was alkaline from the beginning to the end of the tests. MTA BIO presented lower setting time and lower solubility. The cements did not showed a higher solubility than 3%. All the assessed cements showed acceptable values of dimensional variation and high pH during the test time. MTA BIO and ProRoot MTA had adequate radiopacity values.